Melone’s concept revisited in comminuted distal radius fractures: the three-dimensional CT mapping - Shuang Li (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background There is no consensus in the literature about the ideal classification of the distal radius fracture for the clinical practice. The traditional Melone classification system divides the distal radius into four basic components, the shaft, radial styloid, dorsal medial fragment, and volar medial fragment. The aim of this study was to identify fracture lines in comminuted distal radius fractures using three-dimensional mapping of computed tomography (CT) images to test the hypothesis that fracture fragments can be divided according to the Melone classification. Methods Fifty-nine consecutive OTA/AO 23C3 fractures presented at the hospital between January 2018 and October 2019 were retrospectively reviewed. The fracture lines were characterized in the axial, sagittal, and coronal CT planes. After reducing the fractures in a three-dimensional (3D) model, the fracture lines were plotted from the CT images and were then superimposed on one another and oriented to fit a standard template. The area of articular surfaces was measured and compared to quantify the differences between the radial bone fragments. Results Thirty-five cases (59.3%) in this study fit the Melone classification and 24 cases (40.7%) did not. On the radiocarpal surface, there was a greater concentration of fracture lines in the dorsal area of the radius than in the volar area. On the distal radioulnar joint (DRUJ), the fracture lines were focused around two specific concentrated regions. For the articular surface area, the mean area of the radial styloid, volar medial fragment, and dorsal medial fragment was 141.13 ± 90.16 mm2, 147.79 ± 75.94 mm2, and 79.05 ± 70.73 mm2, respectively. There was a significant difference in articular surface area for the Melone fragments (P = 0.002). Conclusions The Melone classification system is not suitable for characterizing all C3 fractures. The findings of this study confirm that the dorsal medial fragments are relatively comminuted and small. Extra care should be given to these small fragments when reducing the fracture.